Sex And Aggression In Peter Flinth's Arn: The Knight Templar Movie (2007): A Psychoanalytic Criticism - Ni'mah, Maftukhatin (2012)
The major problem in this study is to show how sex and aggression in Peter Flinth's Arn: The Knight Templar movie by using psychoanalytic criticism. It is conducted by analyzing the movie based on its structural elements an d based on psychoanalytic criticism. This research is qualitative research. Types of data of the study are text and image taken from two data sources: primary and secondary. The primary data source is Arn: The Knight Templar directed by Peter Flinth released in 2007. While the secondary data sources are taken from the books of literary, internet, and other relevant information. Both data are collected through library research and analyzed by descriptive analysis. Using a psychoanalytic criticism as the theoretical framework, the research shows the following findings. First, based on the structural analysis, it is evident that in this movie Flinth deliver a message that there is always a chance of redemption for the sinner. Second, based on the psychoanalytic analysis, it is evident that in this movie, Flinth wants to convey the psychological phenomenon indicating that personality tends to lead to sex and aggression.